Arahan Peningkatan Kualitas Permukiman Dengan Konsep Healthy Settlements - Azzahra, Aidhea; Kadri, Mohtana Kharisma; Hidayat, Arief; Astha, Dwinsani Pratiwi (COMPACT: Spatial Development Journal, 2024)
Based on the letter issued by the Regent of Berau regarding the determination of the location of housing and slums Number 30 of 2020 stipulates slum locations in 3 (three) areas, settlements located in the Kuyang river area are included in the largest slum with a slum area of 13.89 Ha. Based on the slum decree, there are seven RTs whose buildings are located on the banks and above the river, namely RT 02, 03, 04, 05, 06, 19, and 22, which must be addressed because based on the existing conditions there are still inadequate aspects of the settlement. To achieve safe, orderly, and healthy settlements, environmentally sound settlements are needed with the Healthy settlements concept approach which is expected to determine the direction of improving the quality of settlements in the Kuyang River Area. The data collection method was carried out by primary survey, the analysis used was descriptive qualitative and triangulation techniques. The findings of the research are 3 (three) aspects of Healthy Settlements, namely ecological, social, and economic aspects. Keywords : healthy settlements, criteria, settlement environment